2017
DOI: 10.13031/trans.12345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Four Base Cutter Blade Designs on Sugarcane Stem Cut Quality

Abstract: Abstract. The cut quality of sugarcane stems during harvesting is of considerable importance, as any damage inflicted on the stems and root systems affects ratooning and reduces yield. In current conventional cutting systems for sugarcane, relatively little attention has been paid to optimizing the cutting dynamics by investigating various blade designs and configurations. One limitation of impact cutting methods is the relatively rapid blunting of the blade edges through wear, leading to stem damage. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…At present, the commonly used cutting the end methods can be classified into four types: chain sawing (Copur, 2010), slashing cutter (Johnson et al,2012), reciprocating (Shen et al, 2017) and circular sawing (Momin et al,2017). Different cutting methods are suitable for different materials, and can achieve different cutting effects.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the commonly used cutting the end methods can be classified into four types: chain sawing (Copur, 2010), slashing cutter (Johnson et al,2012), reciprocating (Shen et al, 2017) and circular sawing (Momin et al,2017). Different cutting methods are suitable for different materials, and can achieve different cutting effects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the wear of the blades is influenced by several factors such as, geometry, chemical compositions, the hardness of the work organ's material, speed of work, size and nature of soil particles, and system flaws (e.g. mechanical, hydraulic, and electrical systems) that influences the functional behaviour of the base-cutter blades and, consequently increases wear (Mello and Harris 2003;Cassia et al 2014;Momin et al 2017;Pérez-Reyes et al 2018;Ma et al 2014;de Almeida Silva et al 2020).…”
Section: Quantifying Blade Wearmentioning
confidence: 99%
“…Harvesting quality was assessed based on the damage index (Toledo et al 2013;Momin et al 2017;Xie et al 2019). The damage index is represented by a single classification value, which is attributed to the classification of stalks.…”
Section: Quantifying Harvesting Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, anomputra used the high-pressure water cutting method with abrasive sands added to improve the sugarcane cutting efficiency [12]. Mello [13] and Momin [14] used different blades to carry on experimental research on the sugarcane cutting quality and they found that bendingangle-shape blades with or without saw teeth can improve the sugarcane cutting quality. Ripoli designed a cutter whose cutting depth into soils can be adjusted according to the gradient variation of sugarcane fields [15].…”
Section: Introductionmentioning
confidence: 99%